Soil macrofauna in relation to soil and leaf litter properties in tree plantations - E. Sayad; S.M. Hosseini; V. Hosseini; M.-H. Salehe-Shooshtari (Journal of Forest Science, 2012)
Soil communities exert strong influences on the processing of organic matter and nutrients. Plantations of trees, especially of nitrogen fixing ones, may affect the soil macrofauna through litter quality and quantity. This study was conducted in a randomized block design with three blocks consisting of Populus euphratica, Eucalyptus camaldulensis, Eucalyptus microtheca, Acacia farnesiana, Acacia salicina, Acacia saligna, Acacia stenophylla and Dalbergia sissoo monoculture plantations that were established in 1992. Soils and soil macrofauna were sampled in November 2006. Leaf litterfall was collected from November 2006 to November 2007 at bi-weekly intervals. Macroinvertebrate abundance and biomass were consistently higher in A. salicina plantations than in the others, whereas they were lowest in E. camaldulensis. Tree species and nitrogen fixing trees significantly influenced the soil macrofauna richness. The results suggest that the earthworm distribution is regulated by leaf litter quality (Ca, C and N) whereas the macrofauna richness is regulated by leaf litter mass, soil organic carbon and leaf litter Mg. Totally, it was revealed that the tree species clearly affected macrofauna whereas nitrogen fixation did not.